Cu(Ii)–Gd(Iii) 2d-Coordination Polymer Based on Two Different Organic Linkers - Venegas-Yazigi, D; Venegas-Yazigi, D (Elsevier Ltd, 2017)
A new CuII–GdIII heterometallic coordination polymer was obtained by a two-step synthesis, using the molecular complex [Cu(H2IDC)2(2,2′-bipy)]·2H2O (1) as metalloligand and oxalate as auxiliary ligand (H3IDC = 1H-imidazole-4,5-dicarboxylic acid). The new extended heterometallic network [Gd(H2O)2(C2O4)Cu(IDC)]·H2O (2) crystallizes in a P1¯ triclinic space group presenting a 2D covalent structure. From a structural point of view, (2) can be defined as Gd-zigzag chains [Gd(H2O)2(C2O4)]+ linked by Cu-based molecules, [Cu(IDC)]−. A 3D structure is reached by non-covalent interactions between the layers. Also Gd⋯Cu interlayer interactions through syn–anti carboxylate ligands can be observed. Whereas, from room temperature to 100 K the network behaves as a paramagnet, below 20 K ferromagnetic interactions are observed. The ferromagnetic state was also corroborated by isothermal hysteresis loops measured at 2 K, giving values for Hc and Mr of 50 Oe and 500 emumol−1, respectively. © 2017 Elsevier Ltd